The Berenstain Bears and baby makes five - Berenstain, Stan, 1923-2005.; Berenstain, Jan, 1923- (New York : Random House, 2000)
Sister Bear is upset by all the attention her new baby sister is receiving.
Adult 450
Accelerated Reader AR
Keywords: Babies -- Juvenile fiction; Families -- Juvenile fiction; Bears -- Juvenile fiction